A Study of the Current Scenario of the Obstetrics and Gynecology Residency during the COVID-19 Pandemic - Sonnenfeld, Marina Martinelli; Nozaki, Alexandre Massao; Genova, Anelise Silva de; Ristow, José Ricardo Weitz; Moura, Tamiris Ferreira de; Cabral, Rayanne Pereira [UNESP]; Garcia, João Victor Almeida; Guimarães, Camila Abdias; Oliveira, André Luiz Malavasi Longo de; Francisco, Rossana Pulcineli Vieira (Federação das Associações de Ginecologia e Obstetrícia, 2022)
Objective To analyze the impact of the COVID-19 pandemic on the residency of gynecology and obstetrics in São Paulo. Methods Cross-sectional study developed by representatives of residents of the Association of Gynecology and Obstetrics of the State of São Paulo (SOGESP, in the Portuguese acronym). Data were collected from questionnaires applied to gynecology and obstetrics residents registered on the SOGESP website in February 2022. The interviewees answered about the repercussions of the pandemic on medical residency and whether they had technical and psychological support during the period. Results A total of 247 questionnaires were collected from residents of gynecology and obstetrics. The residents had an age of 28.3 ± 3 years old, and most of them were female (88.4%). The displacement to COVID care was reported by 62.34% of the students, but only 35.6% reported completely adequate personal protective equipment and only 7.7% reported complete theoretical and technical instruction to support these patients. Almost all of the interviewees stated that the gynecology sector was the most affected. The majority of the interviewees considered that the second-year residents had the greatest loss, and more than half of the residents in the 1 st and 2 nd year said they wished to give up their residency during the pandemic. More than 80% of the residents reported online theoretical classes and/or presentation of articles, reinforcing the fact that virtual activities gained a greater space within the medical residency. Conclusion The pandemic impacted the residency in greater proportion in outpatient clinics and gynecological surgeries, also interfering with the physician's desire to continue with the program.
Keywords: COVID-19; gynecology; internship and residency; medical education